Editor's Choice – Dual Antiplatelet Therapy Improves Outcome in Diabetic Patients Undergoing Endovascular Femoropopliteal Stenting for Critical Limb Ischaemia. (March 2017) - Thott, O.; Granath, F.; Malmstedt, J.; Wahlgren, C.-M.
Abstract : Objective: The purpose of this study was to analyse the effect of dual antiplatelet therapy (DAPT) compared to aspirin on outcome after endovascular interventions in patients with CLI. Methods: This was a population based retrospective nationwide cohort analysis. Several linked national databases in Sweden: Swedish National Vascular Registry, Prescribed Drug Registry and National Discharge Registry. A total of 1941 patients (median age 79; range 43–103 years; women 58%) were identified with CLI who had undergone primary femoropopliteal endovascular intervention between 2006 and 2012. Of these, 599 (31%) patients were treated after the intervention with DAPT (aspirin and clopidogrel) and 1342 (69%) patients were treated with aspirin only. Percutaneous transluminal angioplasty (PTA) was performed in 1131 patients (58%), stenting in 633 patients (33%), and subintimal angioplasty (SAP) in 177 patients (9%). Results: DAPT was given after PTA, stenting, and SAP to 17% ( n  = 188), 53% ( n  = 334), and 44% ( n  = 77) of the patients, respectively. During the study period, 77 patients (13%) with DAPT and 228 patients (17%) with aspirin underwent a major amputation. Patients receiving DAPT after stenting had a lower rate of amputation (HR 0.56; 95% CI 0.36–0.86) than patients receiving aspirin alone. In the subgroup analysis, the protective effect of DAPT on amputation seemed to be confined to patients with diabetes mellitus receiving a stent (HR 0.26; 95% CI 0.13–0.52; p  < .001). DAPT after PTA or SAP did not influence limb salvage, and there was no overall difference in mortality. There was no significant difference in bleeding complications between DAPT and aspirin. Conclusion: DAPT with aspirin and clopidogrel compared to aspirin alone was associated with a lower amputation rate but not a higher bleeding rate in patients with diabetes and CLI after endovascular femoropopliteal stenting.